Characterization of Aspergillus fumigatus Extracellular Vesicles and Their Effects on Macrophages and Neutrophils Functions - Souza, Jéssica Amanda Marques; Baltazar, Ludmila de Matos; Carregal, Virgínia Mendes; Gouveia-Eufrasio, Ludmila; de Oliveira, André Gustavo; Dias, Wendell Girard; Campos Rocha, Marina; Rocha de Miranda, Kildare; Malavazi, Iran; Santos, Daniel de Assis; Frézard, Frédéric Jean Georges; de Souza, Daniele da Glória; et al. (Frontiers in Microbiology, 2019)
Extracellular vesicles (EVs) has been considered an alternative process for intercellular communication. EVs release by filamentous fungi and the role of vesicular secretion during fungus-host cells interaction remain unknown. Here, we identified the secretion of EVs from the pathogenic filamentous fungus, Aspergillus fumigatus. Analysis of the structure of EVs demonstrated that A. fumigatus produces round shaped bilayer structures ranging from 100-200 nm size, containing ergosterol and a myriad of proteins involved in REDOX, cell wall remodeling and metabolic functions of the fungus. We demonstrated that macrophages can phagocytose A. fumigatus EVs. Phagocytic cells, stimulated with EVs, increased fungal clearance after A. fumigatus conidia challenge. EVs were also able to induce the production of TNF-α and CCL2 by macrophages and a synergistic effect was observed in the production of these mediators when the cells were challenged with the conidia. In bone marrow-derived neutrophils treated with EVs, there was enhancement of the production of TNF-α and IL-1β in response to conidia. Together, our results demonstrate, for the first time, that A. fumigatus produces EVs containing a diverse set of proteins involved in fungal physiology and virulence. Moreover, EVs are biologically active and stimulate production of inflammatory mediators and fungal clearance.